Wild Dogma: An Examination Of Recent "Evidence" For Dingo Regulation Of Invasive Mesopredator Release In Australia. - Allen, Benjamin L.; Engeman, Richard M.; Allen, Lee R. (DigitalCommons@University of Nebraska - Lincoln, 2011)
There is growing interest in the role that apex predators play in shaping terrestrial ecosystems and maintaining trophic cascades. In line with the mesopredator release hypothesis, Australian dingoes (Canis lupus dingo and hybrids) are assumed by many to regulate the abundance of invasive mesopredators, such as red foxes Vulpes vulpes and feral cats Felis catus, thereby providing indirect benefits to various threatened vertebrates. Several recent papers have claimed to provide evidence for the biodiversity benefits of dingoes in this way. Nevertheless, in this paper we highlight several critical weaknesses in the methodological approaches used in many of these reports, including lack of consideration for seasonal and habitat differences in activity, the complication of simple track-based indices by incorporating difficult-to-meet assumptions, and a reduction in sensitivity for assessing populations by using binary measures rather than potentially continuous measures. Of the 20 studies reviewed, 15 of them (75%) contained serious methodological flaws, which may partly explain the inconclusive nature of the literature investigating interactions between invasive Australian predators. We therefore assert that most of the “growing body of evidence” for mesopredator release is merely an inconclusive growing body of literature only. We encourage those interested in studying the ecological roles of dingoes relative to invasive mesopredators and native prey species to account for the factors we identify, and caution the value of studies that have not done so.